Computational Cell Biology - Fall, Christopher P; Ed. Marland, Eric S; Ed. Wagner, John M; Ed (Springer, 2002)
This textbook provides an introduction to dynamic modeling in molecular cell biology, taking a computational and intuitive approach. Detailed illustrations, examples, and exercises are included throughout the text. Appendices containing mathematical and computational techniques are provided as a reference tool.